An Empirical Investigation Into the Determinants of Various Social Networking Sites Used by Generation Y Consumers - ÇOBANOĞLU, EMİNE; DİRSEHAN, TAŞKIN (My University, 2017)
Social networking sites (SNSs) often propose new marketing channels; generation Y (Gen Y) has an impact on marketing channels today and will continue to do so in the future. Therefore, the authors’ main purpose in this paper is to detect SNS use patterns and to propose new ones that Gen Y commonly uses in Turkey; SNSs include Facebook, Foursquare, Instagram, LinkedIn, and Twitter. To determine SNS use patterns, we adopt a two-step approach that examines uses and gratifications. First, they conduct in-depth interviews with 75 participants, producing 82 items. Then, they test these items on a sample of 740 Gen Y users. This test categorizes Gen Y’s favored SNSs into 13 types. Four of these types are remarkable: “discovery and diary,” “career-related,” “firms and brands,” and “coordination”; these new types are the main original contributions of this study.

Sosyal Ağ Siteleri (SAS) yeni pazarlama kanalları sunmaktadır, Y kuşağı da günümüzde pazarlama kanallarında etkili olmaktadır ve gelecekte bu etki artacaktır. Bu yüzden, yazarların bu çalışmadaki temel amacı, Türkiye’de Y kuşağının genellikle kullandığı; Facebook, Foursquare, LinkedIn ve Twitter’ı kapsayan SAS’lerinin kullanım biçimlerini belirlemek ve bunlara yenilerini önermektir. SAS kullanım biçimlerini belirlemek için kullanımlar ve doyumlar yaklaşımında önerilen iki aşamalı bir yöntem izlenmiştir. Öncelikle 75 katılımcıyla derinlemesine görüşmeler yapılmış ve 82 ifade üretilmiştir. Sonrasında bu ifadeler 740 Y nesli kullanıcısından oluşan bir örneklemde incelenmiştir. 13 farklı Y nesli kullanım ortaya çıkmıştır. Bunlardan dördü dikkat çekicidir ve bu çalışmanın özgün katkısıdır: “Keşif ve kayıt defteri”, “kariyer bağlantılı”, “firmalar ve markalar” ve “koordinasyon”.
Y Kuşağı Tüketiciler Tarafından Kullanılan Çeşitli Sosyal AĞ Sitelerinin (SAS) Belirleyicilerine Yönelik Ampirik Bir İnceleme